2019
DOI: 10.5863/1551-6776-24.4.270
|View full text |Cite
|
Sign up to set email alerts
|

Considerations When Incorporating Technology Into Classroom and Experiential Teaching

Abstract: Technology and education are merging in today's society. Students in primary and secondary education recognize technology incorporated into teaching as a standard practice, not a unique experience. Curriculum standards in professional health sciences education have changed to promote the increased use of technology, with the purpose of enhancing student skills and engagement. The classroom and experiential settings offer opportunities for technology to be incorporated in a variety of ways. Technology can be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Indeed, other studies when assessing VR-based instruction reported similar concerns like discomfort, technical issues, and distractions due to novelty ( 8 ) and discussed various challenges faced during implementing VR ( 7 , 21 25 ). Such challenges and other contributors have impeded the process of incorporating technological advancements into the traditional education paradigm ( 26 28 ). Several reasons for the low acceptance and slow integration of new technologies, specifically VR, in education have been previously discussed ( 29 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other studies when assessing VR-based instruction reported similar concerns like discomfort, technical issues, and distractions due to novelty ( 8 ) and discussed various challenges faced during implementing VR ( 7 , 21 25 ). Such challenges and other contributors have impeded the process of incorporating technological advancements into the traditional education paradigm ( 26 28 ). Several reasons for the low acceptance and slow integration of new technologies, specifically VR, in education have been previously discussed ( 29 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic, however, forced a change in teaching strategies as online instruction became the standard, and teachers had to adjust to it (Mohamad et al, 2020;Mananay et al, 2022). This change has increased awareness of the value of technology in education and drawn attention to the necessity of providing teachers with the training and preparation to use technology in their lesson plans effectively (Spiteri & Rundgren, 2020;Eiland & Todd, 2019).…”
Section: Limited Training and Preparednessmentioning
confidence: 99%
“…For example, many hybrid/ blended and online courses make use of digital technologies to address various course challenges (e.g., reading, engagement, critical thinking). Technology has its pros and cons and often requires the ability to adapt quickly and problem solve technological issues that inevitably arise (Eiland & Todd, 2019). Before adopting a new technology, instructors should determine whether the technology has the potential to solve an educational problem.…”
Section: Personality Characteristicsmentioning
confidence: 99%